Asynchronous sliding mode dissipative control for discrete-time Markov jump systems with application to automotive electronic throttle body control system. (December 2021) - Zhang, Xiang; Zhang, Guangchen; Yin, Yanyan; He, Shuping
Abstract: In this paper, we study the asynchronous observer-based sliding mode control for a class of discrete-time Markov jump systems with time-delay and conic-type nonlinearities. Firstly, we assume there exists a detector described by the hidden Markov model that provides estimated information of the system mode. Based on the detector, a common sliding surface and an observer-based controller are devised. Secondly, we select the appropriate Lyapunov functional and applying linear matrix inequalities techniques to get sufficient conditions such that the controller and observer gains are obtained, which can guarantee the stochastic stability and strict dissipativity of the sliding mode dynamics. Furthermore, the given H ∞ and passive performance are also discussed. Thirdly, to make the system trajectory get to the predetermined sliding surface, a sliding mode control law is proposed. Finally, an application related to the automotive electronic throttle body control system is given to illustrate the correctness and feasibility of this designed approach. Graphical abstract: Highlights: For nonlinear MJSs, the observer-based asynchronous SMC scheme is designed. For the reachability of the sliding surface, a SMC law is given. By a practical example, the effectiveness of this designed approach is illustrated.